2011
DOI: 10.1590/s0103-50532011000800018
|View full text |Cite
|
Sign up to set email alerts
|

Eugenia neonitida Sobral and Eugenia rotundifolia Casar. (Myrtaceae) essential oils: composition, seasonality influence, antioxidant activity and leaf histochemistry

Abstract: Investigou-se a influência da sazonalidade na composição do óleo essencial de folhas frescas de Eugenia neonitida Sobral e Eugenia rotundifolia Casar. (Myrtaceae) coletadas trimestralmente, assim como a atividade antioxidante do óleo essencial de folhas secas e a histoquímica foliar. Os componentes majoritários do óleo essencial de E. neonitida foram biciclogermacreno, germacreno D e b-cariofileno e os de E. rotundifolia foram a-pineno, b-pineno e b-cariofileno. Os óleos essenciais de ambas as espécies apresen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
0
10
0
3
Order By: Relevance
“…In E. rotundifolia oil, the main components were α-pinene, β-pinene, and β-caryophyllene. Seasonality did not significantly interfere in the oils of either species, despite the observed qualitative and quantitative variations [29].…”
Section: Oil Composition and Environmental Conditionsmentioning
confidence: 76%
“…In E. rotundifolia oil, the main components were α-pinene, β-pinene, and β-caryophyllene. Seasonality did not significantly interfere in the oils of either species, despite the observed qualitative and quantitative variations [29].…”
Section: Oil Composition and Environmental Conditionsmentioning
confidence: 76%
“…Moreover, none of the Eugenia species listed in recent review by Stefanello et al 24 showed the presence of epi-longipinanol and 10-epi-g-eudesmol, the major components indentified in the leaf and fruit oils of E. langsdorffii, respectively. On the other hand, the second major component of fruit oil (1,10-epi-cubenol (15.6 ± 0.3%)) was identified in the leaf oil of E. neonitida 25 and Plinia trunciflora 26 in percentage lower than 0.5%.…”
Section: Resultsmentioning
confidence: 96%
“…24 In fact, these oils were characterized by high percentages of sesquiterpenes (72.2 ± 0.9% in leaves and 92.2 ± 0.2% in fruits), followed by monoterpenes. The monoterpne a-pinene and the sesquiterpenes germacrene D, bicyclogermacrene, β-caryophyllene and β-elemene, which were found in Eugenia species as principal components, [24][25][26][27][28][29] were not detected in the leaf and fruit oils of E. langsdorffii. Moreover, none of the Eugenia species listed in recent review by Stefanello et al 24 showed the presence of epi-longipinanol and 10-epi-g-eudesmol, the major components indentified in the leaf and fruit oils of E. langsdorffii, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…(syn. E. umbelliflora ) present two chemical profiles, three specimens collected in Rio de Janeiro and São Paulo states (Brazilian southeast) were shown to be rich in α-pinene (15.8–34.5%) and β-pinene (11.0–34.1%) [ 26 , 27 , 28 ]. The specimen from Santa Catarina (Brazil southern) was rich in viridiflorol (17.7%), followed by β- (13.2%) and α-pinene (11.2%) [ 29 ].…”
Section: Volatile Profilesmentioning
confidence: 99%
“…The oil was mainly composed of cyclic monoterpene and sesquiterpene hydrocarbons, as α-pinene (19.7–34.4%), β-pinene (20.6–34.1%), and ( E )-caryophyllene (3.6–11.7%). The rain precipitation data displayed a significant positive and negative correlation between the ( E )-caryophyllene and α-pinene content, respectively [ 26 ].…”
Section: Seasonal Variation Of Oil Compositionmentioning
confidence: 99%